Ultraestructura de la lesion hepatica en la icterohemoglobinuria bacilar bovina - Garcia, M.G.=700 1 Joa, R.; Bulnes, C.; Gonzalez, A.
(Es, En)
Ilus., 20 ref.
Keywords: GANADO BOVINO; CLOSTRIDIUM; INOCULACION; VACA; NECROSIS; ESTRUCTURA CELULAR; HIGADO; CUBA